Validation of primary metal-on-metal hip arthroplasties on the National Joint Registry for England, Wales and Northern Ireland using data from the London Implant Retrieval Centre: A study using the NJR dataset - Sabah, S. A. (Bone Joint J, 2015)
Arthroplasty registries are important for the surveillance of joint replacements and the evaluation of outcome. Independent validation of registry data ensures high quality. The ability for orthopaedic implant retrieval centres to validate registry data is not known. We analysed data from the National Joint Registry for England, Wales and Northern Ireland (NJR) for primary metal-on-metal hip arthroplasties performed between 2003 and 2013. Records were linked to the London Implant Retrieval Centre (RC) for validation. A total of 67 045 procedures on the NJR and 782 revised pairs of components from the RC were included. We were able to link 476 procedures (60.9%) recorded with the RC to the NJR successfully. However, 306 procedures (39.1%) could not be linked. The outcome recorded by the NJR (as either revised, unrevised or death) for a primary procedure was incorrect in 79 linked cases (16.6%). The rate of registry-retrieval linkage and correct assignment of outcome code improved over time. The rates of error for component reference numbers on the NJR were as follows: femoral head category number 14/229 (5.0%); femoral head batch number 13/232 (5.3%); acetabular component category number 2/293 (0.7%) and acetabular component batch number 24/347 (6.5%). Registry-retrieval linkage provided a novel means for the validation of data, particularly for component fields. This study suggests that NJR reports may underestimate rates of revision for many types of metal-on-metal hip replacement. This is topical given the increasing scope for NJR data. We recommend a system for continuous independent evaluation of the quality and validity of NJR data. Cite this article: Bone Joint J 2015;97-B:10–18.